P584 Mucosal Eosinophilia is an Independent Predictor of Vedolizumab Effectiveness in Ulcerative Colitis. (27th May 2021) - Gremida, A; Huang, K; Ciorba, M; Deyali, C; Deepak, P
Abstract: Background: Ulcerative Colitis (UC) is characterized by intestinal inflammation with chronic inflammatory features. Along with the typical neutrophil-predominant inflammation, there has been growing understanding of the role of eosinophils in UC and the potential therapeutic benefit of Vedolizumab (VDZ) in those cases. VDZ blocks gastrointestinal homing of T lymphocytes and eosinophil recruitment to the intestinal mucosa via blocking α4β7 which plays a major role in eosinophils localization to the intestinal mucosa. We aimed to assess whether mucosal eosinophilia can predict response to VDZ. Methods: A retrospective study in a single IBD center. Active UC patients who were initiated on VDZ were identified. All patients had at least one documented encounter of VDZ infusion, colonoscopy prior to initiation of VDZ and afterwards with mucosal biopsies at both time points. The endoscopic activity was scored using Mayo endoscopic subscore (MES) with remission as MES 0 or 1. Clinical response was assessed using Physician's Global Assessment (PGA) as no response, partial or complete clinical response and clinical remission. Histology was reported by an expert GI pathologist and the response was assessed as none, partial or complete. Mucosal eosinophilia was graded at initial and follow-up biopsies as not conspicuous vs. conspicuous with predominance of eosinophils (>100 eosinophils in at least 2 hpf). Eosinophil activity defined as presence of at least 1 of the 3 histologic features: eosinophilic microabscesses, eosinophilic cryptitis, or degranulated eosinophils Results: 107 UC patients were included in the study with a mean age of 44.9 years, majority were males (N = 61, 55.5%), Caucasians (N = 96, 87.3%) and with pancolonic location (N = 100, 90.9%). Mean disease duration was 11.3 yrs (SD, 8.6). 55.5% of patients had prior aTNF exposure. Clinical remission was observed in (N = 63, 57.3%) and endoscopic remission (N = 73, 66.4%) after initiating VDZ. Complete histological response was observed in (N=50, 46.7%). Baseline characteristics based on endoscopic remission is shown where male sex, disease location and the proportion of patients with conspicuous eosinophils with abnormal activity in mucosal biopsies as well as no improvement in eosinophil activity compared to pre-treatment biopsies is greater among those not in endoscopic remission. In a stepwise backward logistic regression model including sex and disease location, improvement in abnormal eosinophilic activity was independently associated with increased odds of endoscopic remission after initiating vedolizumab (OR 4.3; CI, 1.1 - 16.4, p = 0.03). Conclusion: In ulcerative colitis, change in mucosal eosinophilia after initiating VDZ was an independent predictor of endoscopic remission with VDZ.